Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/vaccines9010028
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy on Social Media: Sentiment Analysis from June 2011 to April 2019

Abstract: Vaccine hesitancy was one of the ten major threats to global health in 2019, according to the World Health Organisation. Nowadays, social media has an important role in the spread of information, misinformation, and disinformation about vaccines. Monitoring vaccine-related conversations on social media could help us to identify the factors that contribute to vaccine confidence in each historical period and geographical area. We used a hybrid approach to perform an opinion-mining analysis on 1,499,227 vaccine-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 34 publications
(26 reference statements)
2
93
0
4
Order By: Relevance
“…Similarly, Hussain and colleagues (2021) found that the overall sentiments of tweets and Facebook posts related to vaccination were positive in the US and UK. In addition, positive tweets showed larger engagement metrics than negative tweets in the present study, which is in line with the findings of Piedrahita-Valdés et al (2021). Moreover, our results showed that vaccine objection and hesitancy were generally more prevalent than vaccine interest, but opinions showed different patterns for each country.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, Hussain and colleagues (2021) found that the overall sentiments of tweets and Facebook posts related to vaccination were positive in the US and UK. In addition, positive tweets showed larger engagement metrics than negative tweets in the present study, which is in line with the findings of Piedrahita-Valdés et al (2021). Moreover, our results showed that vaccine objection and hesitancy were generally more prevalent than vaccine interest, but opinions showed different patterns for each country.…”
Section: Discussionsupporting
confidence: 91%
“…The current COVID-19 pandemic has resulted in a surge of social media use as a forum for discussing an array of topics about the pandemic, including vaccines. Indeed, social media users can be exposed to negative sentiments and misinformation, which may influence individual views and lead to vaccine hesitancy or refusal (Piedrahita-Valdés et al, 2021). Vaccine hesitancy is considered one of the 10 major threats to global health according to the World Health Organization (WHO) (Puri et al, 2020;Kunneman et al, 2020;Piedrahita-Valdés et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, discussions concerning the topic of vaccines has generated false and misleading claims, fake content, and conspiracy theories across the globe [ 31 , 32 , 33 ]. However, contemporary scholarship has demonstrated that misinformation and conspiracy theories can spread much faster on social media compared to mainstream media and these conspiracy theories have influenced the way people think about vaccinations leading the public to question the need for immunization [ 34 ].…”
Section: Background and Contextmentioning
confidence: 99%